The new health insurance solution : - Pilzer, Paul Zane (John Wiley, 2005)
The New Health Insurance Solution explains how you can get better, cheaper, and safer health insurance, and save thousands of dollars a year on all your healthcare costs. The book also explains why you should take your spouse and children off your employer health plan, how to use the new Health Savings Accounts (HSAs) to get a double tax break, how to cut prescription drugs costs by 50% or more, how to get health insurance between jobs, and how to get affordable healthcare for yourself or your parents in retirement